Development and Application of Low-Cost and Eco-Sustainable Bio-Stimulant Containing a New Plant Growth-Promoting Strain Kosakonia pseudosacchari TL13 - Romano, Ida; Ventorino, Valeria; Ambrosino, Patrizia; Testa, Antonino; Chouyia, Fatima Ezzahra; Pepe, Olimpia (Frontiers in Microbiology, 2020)
The use of beneficial microbes as inoculants able to improve fitness, growth and health of plants also in stress conditions is an attractive low-cost and eco-friendly alternative strategy to harmful chemical inputs. Thirteen potential plant growth-promoting bacteria were isolated from the rhizosphere of wheat plants cultivated under drought stress and nitrogen deficiency. Among these, the two isolates TL8 and TL13 showed multiple plant growth promotion activities as production of indol-3-acetic acid (IAA), siderophores, ammonia, and 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase production, the ability to solubilize phosphate as well as exerted antimicrobial activity against plant pathogens as Botrytis spp. and Phytophthora spp. The two selected strains were identified as Kosakonia (K.) pseudosacchari by sequencing of 16S rRNA gene. They resulted also tolerant to abiotic stress and were able to efficiently colonize plant roots as observed in vitro assay under fluorescence microscope. Based on the best PGP properties, the strain K. pseudosacchari TL13 was selected to develop a new microbial based formulate. A sustainable and environmentally friendly process for inoculant production was developed using agro-industrial by-products for microbial growth. Moreover, the application of K. pseudosacchari TL13- based formulates in pot experiment improved growth performance of maize plants.